Inheritance of Some Growth and Yield Traits in Bread Wheat Using Line×Tester Analysis - Ali, Fatih Karim Hama; Abdulkhaleq, Dana Azad (Sulaimani Journal for Pure and Applied Sciences, 2019)
Seven Bread wheat genotypes (Triticum aestivum L.) were used in this investigation.Threegenotypes namely (Maroof, Aras, and Hasad) were used as female parents (lines) and four genotypes namely (Alla, Tamuz-2, Adana and Sabr Beg) were used as male parents (testers).The 12 F1’s hybrids with their 7 parents were evaluated during 2018-2019 growing season.Genotypes were crossed in a line×tester matting in Completely Randomized Block Design (CRBD) with three replicatesat two Locations;Kanipanka and Qlyasan, at Sulaimani city in Iraqi Kurdistan Region.The pooled analysisof variance confirmed that locationhada significant effect on almost all of the studied traits, but it has no effect on grain yield plant-1. The results proved a significant difference between the studid locations in all characters except final yield.At Kanipanka location, Sabr Beg and the cross Maroof×Tamuz-2 granted the highest yield; 26.303 and 23.914 g plant-1respectively.At Qlyasan location Tamuz-2 and the cross Hasad ×Tamuz-2granted the highest yield;19.875 and 19.724 g plant-1 respectively. Tamuz-2 recorded the highest positive General Combining Ability values (2.331and 2.479) for grain yield plant-1 at Kanipanka and Qlyasan, respectively. The cross Maroof ×Tamuz-2 showed the maximum positive SpecificCombiningAbility effect values (3.034) for grain yield plant-1 at Kanipanka, while at Qlyasan the cross Aras×Sabr Beg record the maximum value with 1.743. Testers brought many variations in the expression of the trait grain yield plant-1 at Kanipanka and Qlyasan, respectively.At both locations, the ratio of σ2gca /σ2sca value was less than one (0.062 and 0.450) and the average degree of dominance value was more than one (4.005 and 1.490) which confirmed that non-additive gene effect was in control for the trait grain yield plant-1. The maximum desirable positive heterosis value (26.082) recorded by the crosses Maroof×Tamuz-2 at Kanipanka location, while at Qlyasan location the cross Aras×SabrBegrecorded the maximum desirable positive heterosis value (26.989) for grain yield plant-1.
Keywords: Triticum aestivum L; Genotypes; Line tester analysis; Combining ability; Growth and yield traits